18F-FDOPA PET/CT of Paraganglioma in the Spermatic Cord. (1st May 2023) - Goujon, Anna; Pop, Gabriel; Hissier, Julien; Moreau, Benjamin; Palard-Novello, Xavier
Abstract: A 53-year-old man with chronic kidney failure was referred to perform an 18 F-FDOPA PET/CT to characterize a mass located on the right spermatic cord. Previously, the pathological analysis of CT-guided biopsies suggested paraganglioma or metastatic lesion of pheochromocytoma. Serum normetanephrine and serum metanephrine values were respectively 2- and 1.5-fold greater than the normal upper limit, which could be explained by the chronic kidney failure. PET/CT images revealed intense 18 F-FDOPA uptake of the mass without any other pathological findings, suggesting the diagnosis of paraganglioma. Pathological examination of surgical specimen confirmed the diagnosis of paraganglioma of the spermatic cord, which is exceptional.